Les paradigmes de recherche sur les difficultés dans le travail enseignant - Audrey Murillo; Javier Nuñez Moscoso (Éducation et Socialisation)
This systematic review aims to propose a typology of research on difficulties in teaching work, based on the identification of used paradigms. From a review of French, English and Spanish-speaking works, we highlight five types of paradigms: the psychological, sociological / anthropological, didactic paradigm, work and activity theories, and empiricist. We describe the theoretical and methodological characteristics of these paradigms, as well as the specificities of the studied objects.